1997
DOI: 10.7589/0090-3558-33.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Shell Disease in River Cooters (Pseudemys Concinna) and Yellow–bellied Turtles (Trachemys Scripta) in a Georgia (Usa) Lake

Abstract: A (hsfigurlng shell disease was detected in river cooters (Pseudemys concinna) and yellow-bellied turtles (Trachemys .scripta) from Lake Blackshear, Georgia (USA). The turtles used were part of a mark-recapture study conducted from September 1991 to June 1993. Histologic changes on four turtles included acute segmental necrosis of the epidermis, followed by ulceration, necrosis of the underlying dermis and dermal bone, and exaggerated remodeling of bone. Additional findings included visceral inflammatory lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
1
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 7 publications
1
31
1
4
Order By: Relevance
“…Even though free-ranging turtles were captured in disturbed and polluted sites, animals showed no detectable evidence of clinical disease. The shape of the lesions on the cracked and fractured carapaces is consistent with damage caused by motorboat strikes and show no signs of being caused by pathological agents, as recorded for other freshwater turtles (GARNER et al 1997, KNOTKOVA et al 2005.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Even though free-ranging turtles were captured in disturbed and polluted sites, animals showed no detectable evidence of clinical disease. The shape of the lesions on the cracked and fractured carapaces is consistent with damage caused by motorboat strikes and show no signs of being caused by pathological agents, as recorded for other freshwater turtles (GARNER et al 1997, KNOTKOVA et al 2005.…”
supporting
confidence: 73%
“…Published data of freshwater turtles suffering from necrotic shell diseases (GARNER et al 1997, KNOTKOVA et al 2005 showed higher values of white blood cells, lymphocytes, heterophils and basophils than those obtained for the free-ranging P. geoffroanus in this study. However it is difficult to decide whether the hematological values obtained for P. geoffroanus, in this investigation, are low or normal, since there are no reference range values for free-ranging P. geoffroanus inhabiting unpolluted rivers.…”
contrasting
confidence: 46%
“…Shell necrosis of free-ranging freshwater turtles (Pseudemys and Trachemys spp.) from Lake Blackshear, Georgia, USA, has been reported with acute segmental necrosis of the epidermis, ulceration and necrosis of the underlying dermis and dermal bone, and extensive bone remodeling (Lovich et al, 1996;Garner et al, 1997). Despite visceral inflammatory lesions, and the isolation of various blood-borne bacteria (including Bacteroides, Morganella, and Aeromonas spp.)…”
Section: Introductionmentioning
confidence: 99%
“…Gram-negatif bakteriler yaygın olarak izole edilse de anaerobik bakteriler ve fungal organizmalar da olabilmektedir. 1,17,67 Klinik bulgular olarak anoreksi, letarji, zayıflık, kırmızı-mor oral muköz membranlar ve genel kötü koku septisemiye işaret olabilmektedir. Peteşiyel kanamalar başlangıçta karapaksın kenar plaklarında ortaya çıkmakta, fakat zamanla büyük kanama alanlarına dönüşebilmektedir.…”
Section: Septi̇semi̇unclassified